Perancangan Visualisasi â€œDriver Machine Interface Displayâ€ pada Kereta Api berbasis ATO/ATP menggunakan Aplikasi Visual Studio - Wibiwo, Agustinus Prasetyo; Putra, Febi Wiratama (LPPM STT Terpadu Nurul Fikri, 2021)
The Onboard System is a part of the CBTC's automated routes. Communication Base Interlocking (CBTC) is a train technology system that implements now. The train technology system in Indonesia applies to MRT and LRT trains. On the MRT that is applying Grade Of Automation 2 and LRT apply Grade Of Automation 1. GOA is a system that regulates the automation of train control systems. Onboard System is often an obstacle; namely, the driver has difficulty knowing the train's condition. Therefore, there needs to be a system design that helps the driver know the train's condition. This research method consists of observation, design, and testing of the system. System design makes so that the driver can make it easier to know the train's condition. This research method consists of observation, design, and testing of the system. The system's design makes so that the driver can make it easier to know the condition of the train. Testing is conducted that is a test function receive data from the side of Radio Block Control with On-board can be processed by its function. The test results showed that receiving and processing data on The On-board can be done by its function. From the tests that have conducted with the experiment of 20 route simulations formed by the system, the system was successfully run at a speed of 70 - 90 km and displayed according to inputs from the Radio Block Control database with ATO and ATP modesâ€”assuming a series of 10 trains weighing 38 tons, one locomotive weighing 84 tons and passenger occupancy of 100%.